Effect of a Stepwise Opioid-sparing Analgesic Protocol on In-hospital Oxycodone Use and Discharge Prescription After Cesarean Delivery. Issue 4 (22nd December 2021) - Landau, R.; Romanelli, E.; Daoud, B.; Shatil, B.; Zheng, X.; Corradini, B.; Aubey, J.; Wu, C.; Ha, C.; Guglielminotti, J.
Abstract : ( Reg Anesth Pain Med . 2021;46:151–156) Between 1999 and the 2014, the use of opioids during and after pregnancy increased 5-fold. Between 2007 and 2016, opioid-related deaths during pregnancy tripled. One factor that may contribute to these increasing rates is exposure to opioids during hospitalization after cesarean delivery (CD). Implementing stepwise protocols for analgesia after CD both in-hospital and postdischarge is recommended to help minimize the risk of opioid use. The aim of this study was to examine the effect of a multimodal, stepwise opioid-sparing analgesic order set on oxycodone use in women undergoing CD.